Optimising protein expression via E.coli BL21 (DE3) with the use of bioreactor - Tan, Wei En (2018)
Escherichia Coli (E.Coli) is a popular host of choice for the expression of recombinant proteins. It is widely used in the market or for research as it can be cultured affordably, it is easy to be manipulated and much research has been done on optimizing the factors affecting its growth rate and protein expression yield. It plays an important role in biological pharmaceuticals as it is a key component in many drugs or products meant for therapeutic use, hence the ability for upscale production of E.Coli is imperative. This project aims to optimize the protein expression yield via experimenting on different parameters that affect the growth of E.Coli and use the bioreactor for its upscale production. This project will focus on pH and IPTG induction timing as the parameters were tested and optimized, with all other conditions such as temperature and shake speed being kept constant (37°C at 200rpm). A final extrapolated protein yield of 876.4mg/1L of culture for pH 6 reactor experiment and a yield of 14.25mg/40ml of culture for the IPTG flask experiment was obtained.